PENGARUH PERBEDAAN KOMBINASI DOSIS DAN FREKUENSI PEMBERIAN TRICHOKOMPOS TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Hendra Tampubolon; Armaini Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The development process cocoa cultivation is closely associated with the availability of quality seeds. The quality of the seedlings will determine the growth and production of the commodity. Giving trichocompost TKKS the soil can increase the availability of nutrients both macro and micro. This study aims to determine the effect of the application trichocompost oil palm empty fruit bunches with some frequency of administration and get a dose with a frequency corresponding to the growth of cocoa seedlings (Theobroma cacao L.). This experiments was conducted with non factorial completely randomized design consisting of 6 treatments and three replications. The treatment was P1:trichocompostTKKS dose of 25 g / plant to 1 feedings, P2: trichocompostTKKS dose of 25 g / plant with two feedings, P3: trichocompost TKKS dose of 50 g / plant to 1 feedings, P4: trichocompost TKKS dose of 50 g / plant with two feedings, P5: trichocompostTKKS dose of 75 g / plant to 1 feedings and P6: trichocompost TKKS dose of 75 g / plant with two feedings. The results showed that dose of 75 g / plant TKKS trichocompost at one time significantly affect to the height, number of leaves, stem diameter, leaf area, root volume and dry weight of cocoa seedlings. Keywords : cocoa, trichocompost and frequency